Teleophthalmology: where are we now? - Grisolia,Ana Beatriz D. (2017)
ABSTRACT Information and communication technology has rapidly reached diverse aspects of modern life, including medicine and health-related matters. Aiming to improve teaching, research, and health care delivery for geographic or economic reasons, telemedicine is an ascending trend. Teleophthalmology might be one of the most challenging applications of telemedicine given its need for standardized and high definition digital images. However, technological advances are enhancing information transmission continuously and expanding the potential of teleophthalmology. In this review, we investigate the evolution and current status of teleophthalmology, describe its use in different areas, and explore its applicability. Although teleophthalmology is not a replacement for traditional eye care and still faces challenges for adequate implementation, it represents an effective care delivery method, facilitating appropriate and timely distribution of service especially in remote and/or underdeveloped regions.